NILAI BUDAYA DALAM CERITA RAKYAT MELAYU LEDO DESA LESABELA KECAMATAN LEDO KABUPATEN BENGKAYANG - Reni Yulira; Martono Martono; Sesilia Seli (Universitas Tanjungpura, 2020)
AbstractThis study aims to describe the cultural values contained in Ledo Malay folklore, Lesabela Village, Ledo District, Bengkayang Regency. The problem in this study is how are cultural values viewed from the relationship between humans and God, the relationship between humans and themselves, the relationship between humans and humans, the relationship between humans and nature, and the planned implementation of learning the analysis of cultural values Ledo Malay Folklore in Indonesian language lessons in high school? The method used in this research is descriptive method and this research is in the form of qualitative. The approach used in this research is the sociology of literature approach. The data source in this study is the text of the Ledo Malay folklore (Origin of Ledo, the Legend of Lubuk Selang, and the Legend of Lubuk Semanter), which was obtained from informants or storytellers who came from the Malay Ledo community in Lesabela Village, Ledo District, Bengkayang Regency. Based on the results of data analysis from research that has been done, it can be concluded that: cultural values that reflect human relations with God, human relations with oneself, human relations with humans, and human relationships with nature. In the Ledo Malay folklore, the legend of Lubuk Selang, the Legend of Lubuk Semanter, and the origin of Ledo found in Ledo Hamlet, Lesabela Village, Ledo District, Bengkayang Regency, this research succeeded in collecting 4 analyzes in 3 Ledo Malay folklore consisting of 13 reflection and 24 dataKeywords: Cultural Values, Folklore Oral, Literature, Malay Indo.